Тhe consequences of the modulation instabilities - Kuklin, V.M. (Вопросы атомной науки и техники, 2018)
The paper demonstrates the consequences of modulation instability of intense periodic structures in wave and non-wave media. In the case of a large dissipation level, near and above the threshold, the instability leads to the excitation of spectra whose width narrows, forming narrow spectral lines and self-similar structure of the big spatial clearness. At an insignificant level of dissipation, far from the threshold of modulation instability, the wave motion (initiated by the source) forms anomalous amplitude waves and envelopes exceeding the average amplitude by at three times. The shape of the envelope or wave packet is similar to the shape of Peregrine breather, and the dynamics over time is also similar. The formation of self-similar spatial structures in the developed convection of a thin liquid or gas layer due to the development of modulation instability is presented. In this case, toroidal convection vortices generate poloidal vortices of large scale − the effect of a hydrodynamic dynamo. Experimental results of the investigation of emerging self-similar structures on the graphite surface are presented. The features of the development of parametric instabilities are discussed. Демонструються наслідки модуляційної нестійкості інтенсивних періодичних структур у хвильових і не хвильових середовищах. У разі великого рівня дисипації, поблизу і вище порога формується каскад процесів зі зростаючим часом розвитку і все більшим характерним масштабом, формуючи при цьому самоподібну структуру великої просторової чіткості. При незначному рівні дисипації, далеко від порога хвильовий рух формує хвилі і огинаючі аномальної амплітуди, які в максимумі перевищують середню амплітуду в три рази. Форма огинаючої або хвильового пакету подібна формі брізера Перегріна, при чому динаміка в часі також подібна. Показано формування самоподібних просторових структур у розвиненій конвекції тонкого шару рідини або газу внаслідок розвитку модуляційної нестійкості. При цьому, тороїдальні вихори конвекції генерують полоїдальні вихори великого масштабу – ефект гідродинамічного динамо. Представлено експериментальні результати дослідження самоподібних структур на поверхні графіту. Обговорюються особливості розвитку параметричних нестійкостей. Демонстрируются последствия модуляционной неустойчивости интенсивных периодических структур в волновых и неволновых средах. В случае большого уровня диссипации, вблизи и выше порога неустойчивость представляет собой каскад процессов с увеличивающимся временем развития и все большим характерным масштабом, формируя при этом самоподобную структуру большой пространственной четкости. При незначительном уровне диссипации, вдали от порога волновое движение формирует волны и огибающие аномальной амплитуды, в максимуме превышающие среднюю амплитуду волнения в три раза. Форма огибающей или волнового пакета подобна форме бризера Перегрина, причем динамика во времени так же подобна. Показано формирование самоподобных пространственных структур в развитой конвекции тонкого слоя жидкости или газа вследствие развития модуляционной неустойчивости. При этом, тороидальные вихри конвекции генерируют полоидальные вихри большого масштаба – эффект гидродинамического динамо. Представлены экспериментальные результаты исследования возникающих самоподобных структур на поверхности графита. Обсуждаются особенности развития параметрических неустойчивостей.